Can a ToF-PET photon attenuation reconstruction test stopping-power estimations in proton therapy? A phantom study. (26th October 2021) - Bäumer, C; Bäcker, C M; Conti, M; Fragoso Costa, P; Herrmann, K; Kazek, S L; Jentzen, W; Panin, V; Siegel, S; Teimoorisichani, M; Wulff, J; Timmermann, B
Abstract: Objective . The aim of the phantom study was to validate and to improve the computed tomography (CT) images used for the dose computation in proton therapy. It was tested, if the joint reconstruction of activity and attenuation images of time-of-flight PET (ToF-PET) scans could improve the estimation of the proton stopping-power. Approach . The attenuation images, i.e. CT images with 511 keV gamma-rays ( γ CTs), were jointly reconstructed with activity maps from ToF-PET scans. The β + activity was produced with FDG and in a separate experiment with proton-induced radioactivation. The phantoms contained slabs of tissue substitutes. The use of the γ CTs for the prediction of the beam stopping in proton therapy was based on a linear relationship between the γ -ray attenuation, the electron density, and the stopping-power of fast protons. Main results . The FDG based experiment showed sufficient linearity to detect a bias of bony tissue in the heuristic look-up table, which maps between x-ray CT images and proton stopping-power. γ CTs can be used for dose computation, if the electron density of one type of tissue is provided as a scaling factor. A possible limitation is imposed by the spatial resolution, which is inferior by a factor of 2.5 compared to the one of the x-ray CT. γ CTs can also be derived from off-line, ToF-PET scans subsequent to the application of a proton field with a hypofractionated dose level. Significance. γ CTs are a viable tool to support the estimation of proton stopping with radiotracer-based ToF-PET data from diagnosis or staging. This could be of higher potential relevance in MRI-guided proton therapy. γ CTs could form an alternative approach to make use of in-beam or off-line PET scans of proton-induced β + activity with possible clinical limitations due to the low number of coincidence counts.